Call Auction Transparency and Market Liquidity: Evidence from China1. (18th March 2015) - Gerace, Dionigi; Liu, Qigui; Tian, Gary Gang; Zheng, Willa
Abstract This paper uses the natural experiment offered by the Shanghai Stock Exchange to investigate the impact of opening call auction transparency on market liquidity. We find that the dissemination of indicative trade information during the pre‐open call auction session leads to an overall improvement in stock liquidity in the continuous trading session. Bid‐ask spreads narrow in the first trading hour because adverse selection risk fell significantly and there is less price volatility in the continuous market. This effect is greater for actively traded securities than illiquid securities. Our findings are robust for different lengths of sample period, different lengths of trading hours after market open, and stocks that had (and had not) reformed the share split structure during our research period.